Effect of ozone treatment on lignification and postharvest quality of water bamboo shoots. Issue 4 (17th August 2022) - Liu, Ruiling; Wang, Huizhi; Yang, Hailong; Zhang, Hanqing; Chen, Jisuan; Gao, Haiyan; Chen, Hangjun
Abstract: Ozone treatment is a useful approach to maintain postharvest quality for various fruits and vegetables. In this study, the effects of ozone fumigation on lignification and postharvest quality changes in water bamboo shoots were investigated. Water bamboo shoots were respectively treated with ozone at the concentrations of 0 (control), 3, 6, 9, and 12 µl L −1, packaged in polyethylene packing bag and stored at 2 ± 1°C for 60 days. The results showed that ozone treatment maintained the lightness, whiteness index values and retarded the lignification during storage. Water bamboo shoots treated with 9 µl L −1 ozone showed the best fruit quality and the least lignification. Ozone treatment also slowed the decrease of soluble pectin content and cellulose accumulation by inhibiting the activities of cellulase (Cx) and polygalacturonase. In addition, ozone treatment also protected cell ultrastructure. Ozone treatment could be a potential alternative for inhibiting lignification and delaying quality deterioration of water bamboo shoots during storage. Abstract : Ozone treatment retarded the lignification and delaying quality deterioration of of water bamboo shoots during storage. Ozone treatment also protected cell ultrastructure from oxidative damage.